Des lieux pour un « non-lieu » : Le camp algérien Paul-Cazelles et Hocine Kahouadji, militant FLN - Susan Slyomovics (L’Année du Maghreb)
A set of carceral spaces and politico-legal practices produced during the Algerian War of Independence Algerians without rights. Based on the development of incarceration by French authorities through the continuous and dynamic use of the law, multiple spaces of detainment were created to accommodate populations under the legal condition of “non-lieu” (illegal detention): absent sufficient charges against the indicted party, the investigating judge dismisses the case with “non-lieu.” Despite decisions of “non-lieu” rendered by the French legal system, many Algerian FLN militants arrested in France were kept imprisoned serially in carceral sites and transferred from metropolitan prisons to Algeria’s colonial ones. Although French prison camps in Algeria varied, this essay concentrates on Camp Paul-Cazelles located in Ain Ousseras, 195 km south of Algiers. The focus is on the oral testimony of Hocine Kahouadji, FLN militant.